Analysis of Village Financial Management Supervision (Case Study on The Regional Inspectorate of North Central Timor Regency) - Yoakim Rembu; Yohanes Fritantus (Program Pascasarjana Universitas Negeri Makassar, 2023)
Supervision is a systematic effort by management to compare the predetermined standards performance, plans, or objectives to determine whether performance meets the standards and whether human resources are empowered effectively and efficiently to achieve the objectives as well as a step for corrective actions that need to be taken. Village Financial Management is the activities including planning, implementing, administering, reporting, and accountability of village finances based on the transparency, accountability, and participation principles, which is carried out orderly and budgetary manner. This study aims to analyze the village financial management supervision process conducted by the Regional Inspectorate of North Central Timor Regency. This study used a qualitative approach. The research instrument was the researchers who conducted interviews and interactions in the field by observing the supervision process. The results showed that the Regional Inspectorate has supervised financial management by following the stages namely planning, implementation, reporting, and follow-up. However, the supervision process was not conducted in all village areas due to limited human resources. It was also found that the village government's compliance level in managing village finances was low. It is indicated by the high findings of an inspection conducted by the North Central Timor Regional Inspectorat.